James D. Watson (1928–2025): Influencer of science and society - Jan Witkowski; Bruce Stillman (Proceedings of the National Academy of Sciences, 2026)
James Dewey Watson who died on November 7, 2025, at the age of 97, was a towering figure in 20th century life science. With Francis Crick, he determined the structure of DNA, laying the foundation of modern biology; he made Cold Spring Harbor Laboratory one of the world’s great biomedical research institutes and a center for professional education in molecular biology and neuroscience; he established the Human Genome Project and ensured that research on the associated ethical, legal, and social issues was part of the project; he created a classic textbook that revolutionized the style of the genre; and he wrote one of the most interesting and controversial books on science for scientists and nonscientists alike.